The cruelty is the point : the past, present, and future of Trump's America - Serwer, Adam (One World, 2021)
"Taking joy in suffering is more human than we'd like to admit. The cruelty of the Trump administration's policies and the ritual rhetorical flaying of his targets are intimately connected. Shared cruelty and the delight it brings are critical moments of connection for white supremacists, a fact that is not new. Adam Serwer has been chronicling our political landscape for the last decade. He is one of the most resonant voices of our time, relentless in his pursuit of fact, unsentimental in his storytelling, yet deeply humane in his perspective. At The Atlantic, he has written about the Supreme Court's role in Jim Crow; the history of "white genocide" conspiracy theory; hoaxes; racism; inequality; and of course, Trump. But this collection isn't just about Trump--it's an investigation across centuries interrogating both this moment and its antecedents to reveal the deep roots that have given rise to Trumpism. New material includes four, audience-building essays that expand upon the collection's themes, and unearth more approaches to nationalism and pluralism. Like the polarizing effect Trump's administration has had on American Jews; tracing the emergence of police unions; and making the historical case for abolishing billionaires to preserve American democracy. Additionally, new introductions will provide context and insight into the impact of previously published pieces, why they garnered so much attention amongst media figures, politicians, and social platforms"--